Quorum quenching in anaerobic membrane bioreactor for fouling control - Liu, Jianbo (2020)
Quorum quenching (QQ) is an effective method to control membrane biofouling in aerobic membrane bioreactors (AeMBRs). However, it is not clear if QQ is feasible in an anaerobic membrane bioreactor (AnMBR). In this study, Microbacterium. sp that has QQ capability was embedded in alginate beads, known as QQ beads (QQB), and applied in a lab-scale AnMBR to investigate their potential in fouling control. With the addition of QQB, the operating period of AnMBR-QQB reactor was prolonged by about 8–10 times at constant flux operation before reaching the pre-set maximum transmembrane pressure (TMP). The concentration of Acyl-homoserine lactones (AHLs) in the bulk liquid was significantly higher during the ‘TMP jump’ period compared to QQB and control phases, while AHLs in the membrane foulants were remarkably lower in QQB phase compared to control phase. Furthermore, a much lower level of soluble microbial production (SMP) was observed in QQB phases. Extracellular polymeric substance (EPS), protein in particular, was reduced by 39.73–80.58% in the cake layer of the membrane from QQB phases. Significant changes of organic functional groups were observed in cake layer from QQB membrane as compared with that from control membrane. At the end of operation, bio-polymer (BP), building blocks (BB) and low molecular weight (LMW) organic matters increased in the foulant from control phases but such increase was not observed in QQB phase. After long-term operation, revival of QQB is required due to the declined activity for AHLs degradation.